2021
DOI: 10.1063/5.0021584
|View full text |Cite
|
Sign up to set email alerts
|

Neural modeling of antisaccade performance of healthy controls and early Huntington's disease patients

Abstract: Huntington's disease (HD), a genetically determined neurodegenerative disease, is positively correlated with eye movement abnormalities in decision making. The antisaccade conflict paradigm has been widely used to study response inhibition in eye movements and reliable performance deficits in HD subjects have been observed including greater number and timing of direction errors. We recorded the error rates and response latencies of early HD patients and healthy age-matched controls performing the mirror antisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…This data is in contrast with those of other studies. Prolonged latency and increased latency variability of volitional saccades in presymptomatic carriers was previously noted [12][13][14]. Similar results were obtained by Golding et al, who showed prolonged latency of memory-guided saccades and increased variability of saccades latency [10].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This data is in contrast with those of other studies. Prolonged latency and increased latency variability of volitional saccades in presymptomatic carriers was previously noted [12][13][14]. Similar results were obtained by Golding et al, who showed prolonged latency of memory-guided saccades and increased variability of saccades latency [10].…”
Section: Discussionsupporting
confidence: 86%
“…Saccade disorders are present at an early stage of HD among relatives of patients, and herald the imminent development of the disease [4]. Saccade deficits have been well documented in premanifest and manifest HD patients, and are considered potential biomarkers of disease development and progression [5][6][7][8][9][10][11][12][13][14][15][16][17]. The structural abnormalities of the optic nerve and retina displayed in pre-symptomatic HD carriers could be other potential biomarkers that would be of great interest in HD gene therapies [18].…”
Section: Introductionmentioning
confidence: 99%
“…Next, to remove remaining blinkrelated artefacts, all data ≤ 75 ms either side of all gaps in the data were also deleted. Position data were then filtered using a generalized Savitzky-Golay filter […] Saccades were detected using the method described by Engbert and Kliegl" (Cutsuridis et al, 2021).…”
Section: Item A11: Data Processing Stepsmentioning
confidence: 99%